2022
DOI: 10.3389/fimmu.2022.862866
|View full text |Cite
|
Sign up to set email alerts
|

The Mechanisms of Effector Th Cell Responses Contribute to Treg Cell Function: New Insights into Pathogenesis and Therapy of Asthma

Abstract: CD4 + helper T (Th) cell subsets are critically involved in the pathogenesis of asthma. Naive Th cells differentiate into different subsets under the stimulation of different sets of cytokines, and the differentiation process is dominantly driven by lineage specific transcription factors, such as T-bet (Th1), GATA3 (Th2), RORγt (Th17) and Foxp3 (Treg). The differentiation mechanisms driven by these transcription factors are mutually exclusive, resulting in functional inhibition of these Th subsets to each othe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 98 publications
0
7
0
Order By: Relevance
“…M1-like polarization of macrophages produces large amounts of pro-in ammatory cytokines that affect the balance of the immune system and further trigger a chronic in ammatory response, the mechanism that has been identi ed in both IBD and asthma [28,29]. Meanwhile, Treg cells, a subset of suppressive T cells, play an important role in preventing excessive immune responses, inducing immune tolerance, and preventing and controlling the development of autoimmunity [30,31]; when Treg cells decline in number or become dysfunctional, this can lead to disruption of immune homeostasis and consequently cause autoimmune diseases such as asthma and IBD [32,33].…”
Section: Discussionmentioning
confidence: 99%
“…M1-like polarization of macrophages produces large amounts of pro-in ammatory cytokines that affect the balance of the immune system and further trigger a chronic in ammatory response, the mechanism that has been identi ed in both IBD and asthma [28,29]. Meanwhile, Treg cells, a subset of suppressive T cells, play an important role in preventing excessive immune responses, inducing immune tolerance, and preventing and controlling the development of autoimmunity [30,31]; when Treg cells decline in number or become dysfunctional, this can lead to disruption of immune homeostasis and consequently cause autoimmune diseases such as asthma and IBD [32,33].…”
Section: Discussionmentioning
confidence: 99%
“…This process enhances the production of FOXP3, promoting differentiation in favor of Treg cells ( Peine et al, 2016 ; Griesenauer and Paczesny, 2017 ). Additionally, the regulation of the CCR8 GATA3 receptor facilitates the migration of Tregs to the inflammatory site, thereby promoting asthma control ( Chen W. et al, 2022 ). We have confirmed that OVA-exposed animals exhibited a significant increase in positive staining for FOXP3 compared to the CONTROL group ( p < 0.05).…”
Section: Discussionmentioning
confidence: 99%
“…T regs isolated from CVID patients, when compared to T regs from healthy controls, were enriched in Th response-associated genes, including T cell receptor signaling pathways, and associated with Th17 cell differentiation. T reg cells were shown to regulate all types of Th response, including Th1, Th2, and Th17, and the mutual association of Th and T reg cells currently seems far more complex than the primary concept of effector Th cells and T reg cells inhibiting each other [ 62 , 63 ]. It is thus possible that impaired Ig production in CVID patients is associated with dysregulated Th response control by their T reg cells.…”
Section: Discussionmentioning
confidence: 99%